Palladium-Catalyzed Cyanation of Quinazoline-4-tosylates for Access to 4-CN-Functionalized Quinazolines - Zhao, Xu; Zhou, Yirong; Yang, Qin; Xie, Yepeng; Ding, Qiuping; Deng, Zhihong; Zhang, Ming; Xu, Jingshi; Peng, Yiyuan (Synthesis, 2013)
A highly efficient palladium-catalyzed cyanation of quinazoline-4-tosylates is disclosed. The method is successfully developed for the direct access to various 4-CN-functionalized quinazolines, which are potentially useful as biologically and pharmaceutically active compounds. The reactions were performed under mild conditions using inexpensive copper(I) cyanide as cyano source in good to excellent yields and great functional group diversities.
Keywords: copper; palladium catalysis; quinazoline-4-tosylate